Optical modeling for hybrid visco ferromagnetic electromotive energy flux microscale - Koerpinar, Talat; Koerpinar, Zeliha; Asil, Vedat (Elsevier Gmbh, 2022)
In this article, we describe optical hybrid microfluidic binormal electromagnetic electromotive energy flux microscale in ionospheric plasma. We establish optical hybrid binormal elec-tromagnetic ferromagnetic microscales by using magnetic optimistic density in ionospheric plasma. Also, we obtain hybrid binormal magnetic ferromagnetic optimistic density by hybrid microfluidic visco ferromagnetic binormal magnetic electromotive energy flux microscale. Finally, we construct electromagnetic visco ferromagnetic electromotivemicroscales by hybrid binormal electroosmotic potential of magnetic optimistic potential.
Keywords: Optical fiber; Optical visco ferromagnetic microscale; Visco ferromagnetic model; Electromotive energy flux